Analysis of Community Satisfaction with Public Services in The Bojong Gede District Office, Bogor Regency - Benny Osta Nababan; Akbar Nugroho; Septa Riadi (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
This study aims to determine the level of performance of the service District Office BojongGede as well as to know people's satisfaction with services provided by the District Office of BojongGede and to determine what factors should be corrected in order to be the satisfaction of the community District Office Bojong Gede. The population in this study is the community of the applicant in the District Office BojongGede with a total sample of 100 respondents and determined based on the formula Slovin. Data collection techniques are conducted using surveys and questionnaires, while data analysis using the Software Microsoft Excel 2007 and SPSS version 22 to test the Test Validity, Test Reliability, Service Quality (SQ), Customer Satisfaction Index (CSI), and Importance Performance Analysis ( IPA).The results showed overall service quality (SQ) has a negative gap of 9.69 which means the service provided by the District Office of Bojong Gede not good enough. Then for the value of the index of community satisfaction of the applicant in the District Office BojongGede current is found by 67.27%, which means people feel satisfied with the performance of services provided, but still haven't been to a maximum overall, and on the importance-performance analysis (IPA) contained in the factor cost of services, people are still not satisfied. With this already should District BojongGede Bogor Regency pay attention and be honest about the fairness of the fee provided in order to improve the quality of service and the community be satisfied.